Phase Behaviour and Formation of Fatty Acid Esters Nanoemulsions Containing Piroxicam - Mat Hadzir, Nursyamsyila (Springer US, 2013)
Fatty acid esters are long-chain esters, produced from the reaction of fatty acids and alcohols. They possess potential applications in cosmetic and pharmaceutical formulations due to their excellent wetting behaviour at interfaces and a non-greasy feeling when applied on the skin surfaces. This preliminary work was carried out to construct pseudo-ternary phase diagrams for oleyl laurate, oleyl stearate and oleyl oleate with surfactants and piroxicam. Then, the preparation and optimization study via ‘One-At-A-Time Approach’ were carried out to determine the optimum amount of oil, surfactants and stabilizer using low-energy emulsification method. The results revealed that multi-phase region dominated the three pseudo-ternary phase diagrams. A composition was chosen from each multi-phase region for preparing the nanoemulsions systems containing piroxicam by incorporating a hydrocolloid stabilizer. The results showed that the optimum amount (w/w) of oil for oleyl laurate nanoemulsions was 30 and 20 g (w/w) for oleyl stearate nanoemulsions and oleyl oleate nanoemulsions. For each nanoemulsions system, the amount of mixed surfactants and stabilizer needed for the emulsification to take place was found to be 10 and 0.5 g (w/w), respectively. The emulsification process via high-energy emulsification method successfully produced nano-sized range particles. The nanoemulsions systems passed the centrifugation test and freeze–thaw cycle with no phase failures, and stable for 3 months at various storage temperatures (3°C, 25°C and 45°C). The results proved that the prepared nanoemulsions system cannot be formed spontaneously, and thus, energy input was required to produce nano-sized range particles.